Urinary Concentrating Defect of Adrenal Insufficiency: PERMISSIVE ROLE OF ADRENAL STEROIDS ON THE HYDROOSMOTIC RESPONSE ACROSS THE RABBIT CORTICAL COLLECTING TUBULE - Schwartz, Michael J. (1980)
Mineralo- and glucocorticoid-deficient states, such as Addison's disease, are partly characterized by an inability to generate a maximally concentrated urine. The purpose of the present study was to develop a model of adrenal insufficiency and to determine whether changes in the intrinsic function of the collecting duct could partly account for this concentrating defect. Two kinds of experiments were performed: an assessment of the in vivo ability of adrenal-ectomized rabbits to concentrate their urine, and an examination of the intrinsic hydroosmotic responsiveness of in vitro perfused collecting ducts isolated from normal and adrenalectomized rabbits. The present study demonstrates that adrenalectomized rabbits are unable to concentrate their urine maximally, and that the in vivo administration of either deoxycorticosterone, 250 μg/kg, or dexamethasone, 50 μg/kg, restored to or toward normal their concentrating ability. When cortical collecting tubules from adrenalectomized rabbits were perfused in vitro, they demonstrated a markedly blunted hydroosmotic response to antidiuretic hormone (ADH), which was corrected by the in vitro addition of either aldosterone (50 pM) or dexamethasone (50 pM), but not progesterone (50 pM). The steroids by themselves, in the absence of ADH, had no intrinsic effect on the water permeability of the collecting duct. The blunted hydroosmotic response across cortical collecting tubules from adrenal-ectomized rabbits was corrected by the addition of either 8-bromo cyclic AMP or a potent phosphodiesterase inhibitor, 1-methyl-3-isobutylxanthine. The present studies show that the cortical collecting tubules obtained from adrenalectomized rabbits do not respond normally to ADH. The poor hydroosmotic response to ADH was corrected by exogenous aldosterone, dexamethasone, an analog of cyclic AMP, or a phosphodiesterase inhibitor. In conclusion, the present studies are consistent with the view that the concentrating defect seen in adrenal insufficiency is at least partly the result of the absence of the permissive effect that adrenal steroids exert on the ADH-induced reabsorption of water across the collecting duct. The absence of adrenal steroids results in a diminished rate of cyclic AMP accumulation in the cells of the collecting duct, either as a result of an augmented activity of cyclic AMP phosphodiesterase or a diminished rate of cyclic AMP generation.